2021
DOI: 10.3389/fcell.2021.629430
|View full text |Cite
|
Sign up to set email alerts
|

DAND5 Inactivation Enhances Cardiac Differentiation in Mouse Embryonic Stem Cells

Abstract: Deciphering the clues of a regenerative mechanism for the mammalian adult heart would save millions of lives in the near future. Heart failure due to cardiomyocyte loss is still one of the significant health burdens worldwide. Here, we show the potential of a single molecule, DAND5, in mouse pluripotent stem cell-derived cardiomyocytes specification and proliferation. Dand5 loss-of-function generated the double of cardiac beating foci compared to the wild-type cells. The early formation of cardiac progenitor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 59 publications
(66 reference statements)
3
6
0
Order By: Relevance
“…As previously mentioned, a former study performed on mouse embryonic stem cells, has demonstrated that the suppression of DAND5 leads to an increase in proliferation of cardiomyocytes and drives to a distinct transcriptional profiling sequencing during the first stages of life [21]. In line with this study, we performed an extended structural and molecular analysis of DAND5-KO hiPSC-CMs.…”
Section: Structural and Molecular Analysis Of Dand5-ko Hipsc-cmssupporting
confidence: 55%
See 4 more Smart Citations
“…As previously mentioned, a former study performed on mouse embryonic stem cells, has demonstrated that the suppression of DAND5 leads to an increase in proliferation of cardiomyocytes and drives to a distinct transcriptional profiling sequencing during the first stages of life [21]. In line with this study, we performed an extended structural and molecular analysis of DAND5-KO hiPSC-CMs.…”
Section: Structural and Molecular Analysis Of Dand5-ko Hipsc-cmssupporting
confidence: 55%
“…Mutations in DAND5, such as the heterozygous c.455G>A missense mutation, which decreases DAND5 activity, and the homozygous truncating c.396_397dupCT variant predicted to produce a frameshift protein, have been strongly associated with clinically diagnosed heart malformations [14,22]. In mouse models, it was noticed that, among other cardiac defects, Dand5 loss-of-function promotes the proliferation of cardiomyocytes [18,21]. The hearts of Dand5 knockout mice display ventricular hypertrophy with increased ventricular wall thickness, which causes severe cardiac dysfunction [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations